The Effect of Communication, Organizational Culture, and Conflict on Employee Performance at A Manufacturing Company in Denpasar - Sakti, I Gede Satria Jagat; Ribek, Pande Ketut; Popy Anggreni, Ni Luh; Kristina Andika, Ni Made; Ayu Swandewi, Ni Putu; Puspadewi, Ni Ketut; Viprapastha, Tiksnaya (AIBPM Publisher, 2024)
This research was carried out at PT Astra Honda Motor in Denpasar since there was a lack of coordination between superiors and employees. It can be seen from the fact that there is often overtime without prior notification from superiors so employees feel unprepared and often complain to their superiors. The purpose of this research is to determine and analyze the influence of communication, organizational culture, and conflict on employee performance at PT Astra Honda Motor in Denpasar. The number of samples taken was 92 employees. The analysis techniques used are validity and reliability tests, multiple linear regression analysis, classical assumption test, multiple correlation analysis, coefficient of determination, F test, and t-test. Data processing in this thesis uses the SPSS 30.0 for Windows program. The results of this research show that communication and organizational culture have a positive and significant effect on employee performance at PT Astra Honda Motor in Denpasar. Conflict has a negative and significant effect on employee performance at PT Astra Honda Motor in Denpasar. The implication is that communication and organizational culture have a positive and significant effect on employee performance, while conflict has a negative effect on employee performance at PT Astra Honda Motor in Denpasar